A large observational study of patients with primary immune thrombocytopenia receiving romiplostim in European clinical practice - Steurer, Michael; Quittet, Philippe; Papadaki, Helen A; Selleslag, Dominik; Viallard, Jean-François; Kaiafa, Georgia; Janssens, Ann; Kozak, Tomas; Wadenvik, Hans; Schoonen, Marieke; Belton, Laura; Kreuzbauer, Georg (European journal of haematology, 2017)
OBJECTIVE: Romiplostim has maintained long-term platelet counts in patients with immune thrombocytopenia (ITP) for up to 5 yr in clinical studies. This prospective observational study aimed to describe romiplostim utilisation and outcomes in European clinical practice. METHODS: Adults with primary ITP who received romiplostim in routine care were eligible. RESULTS: Three-hundred and forty patients were eligible for analysis, of whom 299 (88%) completed the 2-yr observation period. The median age was 62 yr, with 43% of patients aged ≥65 yr, and two-thirds of patients initiated romiplostim before splenectomy. The median average weekly dose of romiplostim was 2.8 μg/kg. The median baseline platelet count was 20 × 109 /L, which increased after 2 wk of romiplostim treatment and remained >50 × 109 /L thereafter. After romiplostim initiation, there was a decrease in rates of grade ≥3 bleeding events (from 12 to 2 per 100 patient-years) and ITP-related hospitalisations (from 87 to 33 per 100 patient-years). The rate of thrombotic events was 2 per 100 patient-years, and bone marrow fibrosis occurred in two patients. CONCLUSIONS: Romiplostim dosing, effectiveness and safety in an unselected real-world ITP population seemed comparable with that observed in clinical studies.
Keywords: Female; lidé středního věku; primary immune thrombocytopenia; thrombopoetin; mužské pohlaví; romiplostim; Purpura, Thrombocytopenic, Idiopathic; Receptors, Fc; Humans; Europe; dospělí; Recombinant Fusion Proteins; počet trombocytů; Platelet Count; splenectomy; kombinovaná terapie; observational research; Evropa; lidé; Middle Aged; Thrombopoietin; rekombinantní fúzní proteiny; senioři; receptory Fc; Treatment Outcome; ženské pohlaví; Combined Modality Therapy; Aged; idiopatická trombocytopenická purpura; platelet disorders; Adult; platelet count; Splenectomy; splenektomie; Male; výsledek terapie